2011
DOI: 10.1128/aac.01088-10
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin-Resistant Clinical Isolates of Escherichia coli

Abstract: A surveillance study to identify patients from the community with Escherichia coli resistant to broadspectrum cephalosporins discovered two isolates that were also resistant to polymyxin B and colistin. One isolate from a patient in the community and a second from a patient who received multiple courses of polymyxin B also possessed a CTX-M-15 enzyme. Resistance to cationic peptides in E. coli is unusual, and testing for susceptibility to these agents should be performed.Clinical infections due to multidrug-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…A retrospective chart review of the 19 patients with colistin-resistant isolates in our study revealed that none of them had documented colistin therapy in the 6 months prior to isolation of the organism (data not shown). These results, along with reports of community-associated colistin-resistant Enterobacteriaceae infections (32), underscore the need for a reliable reference method for colistin susceptibility testing. We suggest that BMD with polysorbate 80 should be the reference.…”
Section: Discussionmentioning
confidence: 72%
“…A retrospective chart review of the 19 patients with colistin-resistant isolates in our study revealed that none of them had documented colistin therapy in the 6 months prior to isolation of the organism (data not shown). These results, along with reports of community-associated colistin-resistant Enterobacteriaceae infections (32), underscore the need for a reliable reference method for colistin susceptibility testing. We suggest that BMD with polysorbate 80 should be the reference.…”
Section: Discussionmentioning
confidence: 72%
“…other Gram-negative species, F. novicida is highly resistant to the effects of several antimicrobials, including cationic antimicrobial peptides that disrupt bacterial membranes causing lysis and death (16)(17)(18). These cationic antimicrobial peptides act similarly to polymyxin antibiotics which are often used as surrogates for their study, and F. novicida is also extremely resistant to polymyxins.…”
Section: Significancementioning
confidence: 99%
“…Chiral a,c-diaminobutyric acids are frequently found in various bioactive compounds, such as HA-966 (Cervo et al 2004), L-687414 (Hargreaves et al 1993), polymyxin B (Urban et al 2011), and synthetic inhibitors (Belliotti et al 2005;Field et al 2007) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%